2012
DOI: 10.3892/mmr.2012.876
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma and p53 protein expression in pre-malignant oral lesions and oral squamous cell carcinoma

Abstract: Abstract. The retinoblastoma (Rb) and p53 genes play a fundamental role in cell cycle mechanisms, and their deregulation is related to many steps of oral cancer carcinogenesis. This study was conducted to evaluate the expression of the p53 and Rb proteins in malignant and pre-malignant oral cavity lesions. This retrospective study was conducted at the Federal University of Bahia, Salvador, Brazil, and the Molecular Biology Laboratory of the Otorhinolaryngology Department at the University of Heidelberg, Heidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Many studies on oral premalignant and malignant lesions have shown p53 overexpression ranging from 35% to 90% [ 13 , 15 , 27 , 28 ]. Overexpression in OLs was further confirmed in recent studies [ 29 - 33 ]. In particular, De Oliveira et al analyzed p53 protein expression in OSCC and premalignant lesions.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Many studies on oral premalignant and malignant lesions have shown p53 overexpression ranging from 35% to 90% [ 13 , 15 , 27 , 28 ]. Overexpression in OLs was further confirmed in recent studies [ 29 - 33 ]. In particular, De Oliveira et al analyzed p53 protein expression in OSCC and premalignant lesions.…”
Section: Discussionsupporting
confidence: 71%
“…They found a higher expression of p53 protein in OLs with respect to OSCC lesions (55.2 vs . 44.8%) and emphasized the key role of p53 during early stages of carcinogenesis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Rb percentage 1-10% showing weak staining for Rb protein was considered as Rb negative and >10% was considered as Rb positive. [ 12 ] As the mean expression of Rb in the various groups of oral lesions was recorded, the Rb positive group was not graded percentage wise.…”
Section: Methodsmentioning
confidence: 99%
“…Although the alteration in Rb protein expression in tumorigenesis has not been completely elucidated, there is increasing evidence that Rb protein pathway is rendered dysfunctional in oral cancer. [ 12 ] The strong role of pRb in cell cycle regulation prompted us to take up this study, with the aim of assessing the role of Rb protein in the progression of oral cancer, by indicating its expression in the spectrum of lesions ranging from normal to the different histological types of oral cancers. The study also correlates the expression of Rb protein with the clinicopathological parameters including habits like smoking, Paan chewing and alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) pathways were shown in previous pre-clinical studies to have a major role in SCCHN carcinogenesis by regulating p53 and Rb gene expression. p53 and Rb are regulators of cell cycle control, cell proliferation and apoptosis [14], [15]. More recently, cetuximab, an IgG1 monoclonal antibody against the extracellular portion of the epidermal growth factor receptor (EGFR), was extensively studied in this field [9], [13], [16].…”
Section: Introductionmentioning
confidence: 99%